The Thwarting of Laplace's Demon - Green, R. author. aut Link
XII, 229 p.
Keywords: Laplace (1849-1827) was the famous French astronomer and mathematician who outspokenly proposed that every occurrence is in every respect determined by laws of nature - that all that exists is determinate. This book aims to show how the mechanistic framework of ideas associated with modern science distorts our understanding not only of the human mind but of the fundamental attributes of life itself. Before we can rid ourselves of this distorting influence our very notion of causality needs to be clarified and changed. The book sets out a proposal of what is required. The book's many arguments have profound implications not only for philosophy, but for neuropsychology, biology and biophysics.